OPTIMALISASI BOTOL 600 ML PADA MESIN BLOW MOLDING DENGAN RSM (RESPONSE SURFACE METHODOLOGY) - Surya, Surya Apriyanto; Mas'ud, Mochamad (ELEMEN : JURNAL TEKNIK MESIN, 2023)
PT. TL Pasuruan is a company operating to produce bottled mineral water products. The type of product that is often produced is mineral water in 600 ml bottles using preform materials. The problem occurs when the material is replaced from type B to type A, the effect is that there are many defects caused by the temperature of the heater not matching the type of material used before. This research method is the Response Surface Methodology. The type of factorial design used is Box Behnken Design (BBD) with Minitab 21 software. The results obtained using Minitab software are 54 runs. The results of the study using the response surface method obtained the parameter settings for zone 1 = 164.7475℃, zone 2 = 137.8990℃, zone 3 = 74.4242℃, zone 4 = 76.8081℃, cycle time = 4.2485 (s) and blowing time = 1.250 (s). The product quality response variable is 0.6845 with a desirability of 1.000.